(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2022)
This essay outlines the European Union’s basic approaches to gender equality. Based on formal and substantive equality, the European Commission pursues a dual approach by integrating a gender perspective into contemporary social trends and by initiating specific measures. Gender mainstreaming is the integration of a gender equality perspective into every phase of the political process - design, implementation, monitoring and evaluation - in order to improve equality between women and men. This means assessing the impact of policies on women and men and, if necessary, taking steps to change policies. The goal is to make gender equality a reality and to improve the process of creating policies by bringing them closer to the needs of the citizens. The result of the systematic integration of the priorities and needs of women and men in all policies is in order to promote equality between women and men and to mobilize all general policies and specific measures to achieve equality and to actively and openly take into account planning phase their effects on the situation of women and men separately in implementation, monitoring and evaluation.